Socioeconomic Development: Search For Optimal Models For Forecasting Inflationary Processes - Gasparian, Mikhail Samuilovich; Kiseleva, Irina Anatolievna; Titov, Valeriy Aleksandrovich; Sysoev, Nikita Aleksandrovich; Chernysheva, Elena Nikolaevna (International Journal of Criminology and Sociology, 2021)
The article is devoted to the analysis of the forecasting models for inflationary processes. The monetarist approach to inflation has been discussed in the article, and the inflation forecasting tools have been classified. Various inflation forecasting models have been studied, namely, one-factor models, Phillips-curve-motivated forecasts, vector autoregressive models, and dynamic models of general equilibrium. Comparative characteristics of the quality of the inflation forecasting models have been provided.